The Lived Experience of Financialization at the UK Financial Fringe - APPLEYARD, LINDSEY; PACKMAN, CARL; LAZELL, JORDON; ASLAM, HUSSAN (Journal of social policy, 2023)
The financialization of everyday life has received considerable attention since the 2008 global financial crisis. Financialization is thought to have created active financial subjects through the ability to participate in mainstream financial services. While the lived experience of these mainstream financial subjects has been the subject of close scrutiny, the experiences of financial subjects at the financial fringe have been rarely considered. In the UK, for example, the introduction of High-Cost, Short-Term Credit [HCSTC] or payday loan regulation was designed to protect vulnerable people from accessing unaffordable credit. Exploring the impact of HCSTC regulation is important due to the dramatic decline of the high-cost credit market which helped meet essential needs in an era of austerity. As such, the paper examines the impact of the HCSTC regulation on sixty-four financially marginalized individuals in the UK that are unable to access payday loans. First, we identify the range of socioeconomic strategies that individuals employ to manage their finances to create a typology of financial subjectivity at the financial fringe. Second, we demonstrate how the temporal and precarious nature of financial inclusion at the financial fringe adds nuance to existing debates of the everyday lived experience of financialization.